Pemberdayaan Masyarakat Dalam Promosi Lilin Aromaterapi Di Wilayah Sukaraja Kabupaten Seluma Tahun 2023 - Nugroho, Nehru; Riyadi, Agung; Pardosi, Pardosi (Utami Publisher, 2024)
Aromatherapy is one of the non-pharmacological interventions that nurses pay attention to.** Aromatherapy is a healing method that uses highly concentrated essential oils with fragrant aromas extracted from plant essences. The primary components of the oils provide a distinct aroma or scent, which is obtained from a specific plant (Geddes, 2000). Aromatherapy is composed of various types of volatile plants extracted from sources such as flowers, leaves, wood, roots, bark, and other plant parts. In more detail, aromatherapy is a form of treatment using volatile plant aromas (Yoshiko and Purwoko, 2016). Aromatherapy can come in the form of liquid or aromatherapy candles. Naturally derived aromatherapy candles are preferable compared to synthetic air fresheners, which may actually harm the health of those who inhale them (Minah et al., 2017).Coffee-scented aromatherapy candles can be made by coffee farmers as an additional product, besides coffee as a beverage. Roasted coffee, once ground into powder, can be combined with wax to create coffee-scented candles. Attractive production and packaging can increase the selling value of coffee-scented aromatherapy candles, especially if they are used in patient interventions in hospitals.This community service activity in the field of entrepreneurship aims to develop coffee products into coffee-scented aromatherapy candles and train students to become entrepreneurs and creative product developers. The target audience for this activity is nursing students at the Bengkulu Polytechnic of Health and coffee farmers.